Itch in Atopic Dermatitis – What Is New? - Legat, Franz J. (Frontiers in Medicine, 2021)
Atopic dermatitis (AD) is among the most frequent inflammatory skin diseases in humans, affecting up to 20% of children and 10% of adults in higher income countries. Chronic pruritus is a disease-defining symptom of AD, representing the most burdensome symptom for patients. Severe chronic pruritus causes significant sleep disturbances and impaired quality of life, as well as increased anxiety, depression and suicidal behavior. Until recently, skin care, topical corticosteroids, and calcineurin-inhibitors were primarily used to treat mild to moderate AD, while phototherapy and immunosuppressive agents such as corticosteroids, cyclosporine, and methotrexate were used to treat patients with moderate to severe AD. The potential short- and long-term adverse events associated with these treatments or their insufficient therapeutic efficacy limited their use in controlling pruritus and eczema in AD patients over longer periods of time. As our understanding of AD pathophysiology has improved and new systemic and topical treatments have appeared on the market, targeting specific cytokines, receptors, or their intracellular signaling, a new era in atopic dermatitis and pruritus therapy has begun. This review highlights new developments in AD treatment, placing a specific focus on their anti-pruritic effects.